Maternal effects do not resolve the paradox of stasis in birth weight in a wild red deer populaton. (1st November 2022) - Gauzere, Julie; Pemberton, Josephine M.; Kruuk, Loeske E. B.; Morris, Alison; Morris, Sean; Walling, Craig A.
Abstract: In natural populations, quantitative traits seldom show short‐term evolution at the rate predicted by evolutionary models. Resolving this "paradox of stasis" is a key goal in evolutionary biology, as it directly challenges our capacity to predict evolutionary change. One particularly promising hypothesis to explain the lack of evolutionary responses in a key offspring trait, body weight, is that positive selection on juveniles is counterbalanced by selection against maternal investment in offspring growth, given that reproduction is costly for the mothers. Here, we used data from one of the longest individual‐based studies of a wild mammal population to test this hypothesis. We first showed that despite positive directional selection on birth weight, and heritable variation for this trait, no genetic change has been observed for birth weight over the past 47 years in the study population. Contrarily to our expectation, we found no evidence of selection against maternal investment in birth weight—if anything, selection favors mothers that produce large calves. Accordingly, we show that genetic change in birth weight over the study period is actually lower than that predicted from models including selection on maternal performance; ultimately our analysis here only deepens rather than resolves the paradox of stasis.